Typically Developing Preschoolers' Behavior Toward Peers With Disabilities in Inclusive Classroom Contexts. (March 2020) - Hong, Soo-Young; Eum, Jungwon; Long, Yanjie; Wu, Chaorong; Welch, Greg
This study aimed to investigate typically developing preschoolers' behavior toward peers with disabilities in inclusive classrooms, focusing on the co-occurrence of the interactions between children with and without disabilities with various classroom contexts. Behaviors of 22 typically developing preschoolers were observed and coded on two different days in both indoor and outdoor classrooms during free play, small group activities, transitions, and meals/snack. Typically developing children interacted with peers with disabilities for a small amount of time; the interactions were significantly more likely in the outdoor classroom, in either child- or teacher-directed activities, and in play activities. There was a lack of adults' intentional scaffolding for social interactions between children with and without disabilities even when they were near the children. Activity contexts contribute to children's social behavior, and teachers need more support and training with inclusive and collaborative practices.